ANALISIS MEDIA SOSIAL DAN KONSUMEN PADA UMKM CROFFLE EAT BENGKONG - Flowerensia, Dionna; Jessy; Permata, Nadiva Surya; Rovina; Sinambela, Fitriana Aidnilla; Fahlevi, Renza (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
Croffle Eat SME is a snack type business, namely croffle, which is located in Bengkong Laut. This business has been established since 2021, but it seems that there are still many people who don't know the Croffle Eat brand. Therefore, this research was conducted to help partners develop their business through the use of digital marketing such as building brand profiles on social media and advertising to increase consumer interest. As for the things that are done to increase sales turnover at Croffle Eat, namely by implementing the promotion mix strategy. Based on the results of an analysis of the obstacles experienced by partners, it was found that there were obstacles, namely the lack of promotion on social media which caused weak brand awareness in these MSMEs. Therefore, this research was conducted to integrate the implementation of the promotion mix marketing strategy by creating interesting content along with the right consumer targeting and in accordance with the results of a consumer survey to increase partner sales.